Feeding behavior in freshwater bryozoans: function, form, and flow. Issue 2 (19th May 2016) - Tamberg, Yuta; Shunatova, Natalia
Abstract: Bryozoans are impressively active suspension feeders, with diverse feeding behaviors. These have been studied extensively in marine bryozoans, but less so in their freshwater counterparts. Here we identified 16 distinct behaviors in three phylactolaemate species and classified them into behaviors involving separate tentacles, groups of tentacles, lophophore arms, the introvert, or multiple zooids. We examined (1) the repertoire of behaviors in each species, and each behavior's (2) absolute frequency, (3) relative frequency and (4) duration in each of the three species, at two flow velocities (0 and 0.2 cm s −1 ). Nine feeding behaviors were shared by all three species, but the occurrence of other behaviors in a given species was limited by its morphology. Behaviors involved in particle capture were the most frequent, and were often faster than the reactions involved in particle rejection. By contrast, the absolute frequency of behaviors varied widely among species without clear associations with species form, or function of the behavior. Flow velocity had only minor effects on the feeding behaviors exhibited by a species, or their frequencies or durations. Our results show that phylactolaemates have the same key feeding behaviors of the individual polypides (especially involving separate tentacles) as previously described in gymnolaemate and stenolaemate bryozoans, although their behaviors tend to be carried out more slowly than those of stenolaemates or gymnolaemates. Feeding behaviors involving multiple zooids were nearly absent in the studied phylactolaemates, but are common in gymnolaemates. Freshwater bryozoans appear to be intermediate between stenolaemate and gymnolaemate bryozoans in terms of richness of the repertoire of feeding behaviors.